THE ANALYSIS OF THE EFFECTIVENESS AND CONTRIBUTION OF REGIONAL RETRIBUTION TOWARDS OWN-SOURCE REVENUE (OSR) (A Study in Office for Management of Regional Financial of Klaten Regency) - Christanti, Paramita Lea (KIAT BISNIS, 2016)
This research aimed to analyze the effectiveness and contribution of regional retribution towards Own-Source Revenue (OSR). Also, this research aimed to provide solution upon the research problem on how the effectiveness, contribution and revenue growth rate of Regional Retribution as one of sources of Klaten Regencyâs OSR. More specifically, this researchâs purpose was to analyze the potency of Klaten Regencyâs regional retribution revenue in the period of 2017-2018. In this descriptive research, the researcher conducted interview and documentation as the technique of data collection. In addition, this research was conducted in Office for Management of Revenue and Finance of Klaten Regency at Jl. Pemuda No. 294 South Klaten, Klaten, West Java.The results of this research were: 93% of regional retribution revenue was averagely effective, whereas the growth rate of permit public service retribution averagely increased to 4% per year. Meanwhile, the growth rate of business service retribution was improved to 9% per year. Greater than that, this research figured out that the growth rate of permit service retribution rose amounted to 23% per year. As for the period of 2011-2016, the average growth of public service retribution was amounted to 4% per year, which was slightly below business service retribution (9%). Once again, permit service retribution lead the growth revenue by 23% per year. Furthermore, by using least square method, the researchers projected the 2017 regional retribution revenue was amounted to 23.949.742.196 and 24.825.725.602 in 2018. Keywords: Regional Retribution, Own-Source Revenue, Effectiveness, Contribution